Model Sistem Pengendalian Suhu dan Kelembaban Ruangan Produksi Obat Berbasis NodeMCU ESP32 - Khalifa, Arfend Atma Maulana; Prawiroredjo, Kiki (P3M Politeknik Negeri Banjarmasin, 2022)
Production process in a pharmaceutical industry must follow the guidelines stated in Current Good Manufacturing Practice (CGMP). The production process has to be stopped if the temperature and the humidity of the production room do not meet the set point and a report about the caused has to be made. This research proposed a model of a temperature and humidity automatic control system based on Node MCU ESP32 and give the information to technicians continuously. With the php MyAdmin Web Server connection, data of temperature and humidity can be stored and monitored remotely using a smartphone or a computer. A DHT 11 sensor is used to detect temperature and humidity, a Peltier fan is used to control the room temperature and a dehumidifier is used to control the air humidity. The system controls C and D production class room according to CGMP for liquid drug type in a sterile room. The C class drug production room temperature range is set from 16ËšC to 25ËšC and the air humidity range is 45% to 55%. The D class drug production room temperature range is set 20ËšC to 27ËšC and the air humidity range is 40% to 60%. From the test results, it can be seen that the system can control room temperature and humidity automatically when there are disturbances as well as recording the time when the disturbances occur to complete the data reports during the drug production process.